Pengembangan Budaya Keagamaan Pesantren Studi Kasus di Pondok Pesantren Terpadu Bustanul Arifin dan Nurul Islam Bener Meriah - Hakim Mustaqim, Muhammad; Abdussyukur (Jumper: Journal of Educational Multidisciplinary Research, 2024)
The educational efforts in Indonesia, including Islamic boarding schools, in religious culture have become a formidable challenge. The Islamic Boarding School of Bustanul Arifin and Nurul Islam already have distinctive religious cultures through the programs developed in Islamic Boarding Schools. This study aims to determine the program of religious culture and the implementation of religious culture. This study uses a descriptive-comparative method. The data collection was obtained through interviews, observation, and documentation. The data analysis is used by inductive analysis. The data were analyzed using the Bourdieu habitus approach. The research results are as follows: First, the culture at the Islamic boarding school of Bustanul Arifin is moral, salaf culture, santri discipline culture, and Sanadan culture. The Islamic boarding school of Nurul Islam has a moral culture, clean culture, language culture, ubudiyah culture, and annual culture. Second, the implementation of religious culture at the Islamic boarding school of Bustanul Arifin is a moral culture by developing respect and honouring teachers, efforts to serve students, the mandatory wearing of hats, salaf culture with the development of sorogan culture, deliberation, memorizing of nahwu Sharaf, Malay Arabic, student discipline culture by using audio speakers, ceremonies and cults, the culture of Sanadan with a reading of musalsal hadiths. The implementation of religious culture in the Islamic boarding school of Nurul Islam is a moral culture using teacher advice, clean culture utilizing the development of room pickets, rayon pickets, and clean Fridays, language culture using Arabic and English language (muhadatsah, picket Bawab), ubudiyah culture using tajhiz mayit, the assignment of a preacher, obligatory memorization (short verses and prayers), annual culture uses khutbatul arsyi, tadris amaliyah, and community service practices.